Inquiring the Environmental Phillips Curve: The Case of Selected Asian Countries (Journal of Asian Development Studies, 2025)
Environmental quality is among one of the major macroeconomic and environmental challenges of present time. The increasing share of carbon emissions in the air has led climatic and health related issues around the world. This research is conducted to see the roles of unemployment, regulatory quality, total natural resource rent and population density upon carbon emissions in the selected Asian Economies. The interlink between unemployment and carbon emissions will guide us about the presence/absence of Environmental Phillips curve. This study considers the cross-sectional autoregressive distributed technique over the period from 1990 to 2024 and provides the evidence of trade-off between unemployment and environmental degradation. The results further demonstrates that unemployment significantly mitigate carbon emissions and hence confirms the trade-off relation. These findings provide evidence of Environmental Phillips Curve in Selected Asian Economies. Moreover, the findings also highlight that rents from natural resources significantly accelerate carbon emissions while regulatory quality as measure of institutional quality expands carbon emissions. Based on these findings, this research proposes that unemployment may be reduced, rents from natural resources may be increased and quality of regulations are improved in such a way that it should not trigger carbon emissions in the selected sample countries.